Pengaruh Kompetensi dan Kualitas Pegawai terhadap Kinerja Pegawai pada Pusat Pendidikan dan Pelatihan Badan Pusat Statistik - Fauzan Azis; Zaharuddin Zaharuddin; Suhardi Suhardi (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Employee performance is a critical factor in ensuring the effectiveness of organizational activities, particularly within public institutions responsible for developing human resources. However, variations in employee performance may arise due to differences in competence and employee quality. This study aims to analyze the influence of employee competence and employee quality on employee performance at the Education and Training Center of the Central Statistics Agency. The research applied a quantitative approach with a descriptive and associative design. The population consisted of 104 employees, while the sample included 100 employees selected using a total sampling technique. Data were analyzed using multiple linear regression, supported by partial (t-test), simultaneous (F-test), and coefficient of determination analysis. The findings indicate that competence has a significant effect on employee performance, as evidenced by a t-value of 9.773 which is greater than the critical value of 1.983. Employee quality also significantly influences performance with a t-value of 10.755 exceeding the critical value of 1.983. Simultaneously, competence and employee quality significantly affect employee performance with an F-value of 390.320 and a significance level of 0.000. The coefficient of determination shows that 88.9% of employee performance is explained by competence and employee quality, while the remaining 11.1% is influenced by other factors outside the model.